2008
DOI: 10.1590/s0021-75572008000600011
|View full text |Cite
|
Sign up to set email alerts
|

Validade concorrente e confiabilidade da Alberta Infant Motor Scale em lactentes nascidos prematuros

Abstract: Objective: To verify the concurrent validity and interobserver reliability of the Alberta Infant Motor Scale (AIMS) in premature infants followed-up at the outpatient clinic of Instituto Fernandes Figueira, Fundação Oswaldo Cruz (IFF/ Fiocruz), in Rio de Janeiro, Brazil. infants between 0 and 18 months were assessed using the Alberta Infant Motor Scale, by two different observers and the results analyzed using the intraclass correlation coefficient. Methods Results:The concurrent validity study found a high le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
2
6
0
7
Order By: Relevance
“…Although the research tool was not the Bayley-II, it has been shown in the literature that there is a high correlation between the raw scores of the AIMS and the Bayley-II motor scale. 25 In the present study, the findings in relation to expressive communication indicated that there was a tendency for preterm infants to present a poorer linguistic repertoire, in comparison with fullterm infants, and this result was similar to what was described by Schirmer et al 26 Language developmental disorders are among the risks that prematurity may cause, and extreme prematurity tends to bring about even worse results, especially among males. 27 In relation to the premature group in this sample, a number of important biological findings stand out: the mean gestational age of the group was 33 weeks, thus classifying the majority of the infants as moderately preterm, with a mean birth weight of 1762 g. The lowest Apgar score was 4, thus representing moderate to good birth vitality, and also confirming that the frequency of perinatal and postnatal morbidity was low.…”
Section: Resultssupporting
confidence: 91%
“…Although the research tool was not the Bayley-II, it has been shown in the literature that there is a high correlation between the raw scores of the AIMS and the Bayley-II motor scale. 25 In the present study, the findings in relation to expressive communication indicated that there was a tendency for preterm infants to present a poorer linguistic repertoire, in comparison with fullterm infants, and this result was similar to what was described by Schirmer et al 26 Language developmental disorders are among the risks that prematurity may cause, and extreme prematurity tends to bring about even worse results, especially among males. 27 In relation to the premature group in this sample, a number of important biological findings stand out: the mean gestational age of the group was 33 weeks, thus classifying the majority of the infants as moderately preterm, with a mean birth weight of 1762 g. The lowest Apgar score was 4, thus representing moderate to good birth vitality, and also confirming that the frequency of perinatal and postnatal morbidity was low.…”
Section: Resultssupporting
confidence: 91%
“…During the early years of the child's life, motor and cognitive development seems to be synchronous, particularly from the six months of age 9 . Statistically significant correlation between the results of the AIMS and Bayley-II scales in children at 6 and 12 months 28 and in preterm infants of 12 and 18 months 29 have been reported, confirming our results. Recent study found a positive correlation of motor skills with cognitive skills 30 , a result similar to the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Os critérios analisados nas diferentes posturas são o alinhamento postural, a descarga de peso e os movimentos antigravitacionais. A AIMS é considerada válida para a população brasileira (GONTIJO; MAGALHÂES; GUERRA, 2014) e apresenta bons índices de confiabilidade, consistência e poder de discriminação (VALENTINI; SACCANI, 2012), além de alta concordância intra e interexaminadores (ALMEIDA et al, 2008;SACCANI, 2011).…”
Section: Alberta Infant Motor Scaleunclassified